Enhancing xylose utilisation during fermentation by engineering recombinant Saccharomyces cerevisiae strains - Thanvanthri Gururajan, Vasudevan (Stellenbosch : Stellenbosch University, 2012)
Dissertation (DPhil)--University of Stellenbosch, 2007.